STRATEGI GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA UNTUK MENGEMBANGKAN LITERASI ANAK USIA DINI - Rahma, A. Aulia; Bafadal, Usman; Ilyas, Sitti Nurhidayah; Musi, Muhammad Akil; Rusmayadi (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
Literacy development is a fundamental aspect to be instilled in children from an early age. With the enactment of the Merdeka Curriculum policy, it encourages the need for strategies in its implementation. This curriculum provides flexibility for teachers to adjust teaching strategies to be more effective in developing children's literacy. This study uses a descriptive qualitative method, aims to identify, and describe the teacher's strategy in implementing the Merdeka Curriculum to develop children's literacy skills. Data were collected through observation, interviews, and documentation. The results showed that teachers use several strategies in implementing the independent curriculum to develop children's literacy, including the strategy of actively involving children in play activities, storytelling activities or stimulation by talking, using technological media, the teacher's role is quite large in optimizing children's literacy skills, so that children show good literacy skills such as being able to recognize letters, read, write, count and recognize numbers, and being able to express their opinions. The implication of this study shows that teachers need to have strategies in implementing the Merdeka Curriculum and utilizing various learning media to foster children's ability to literacy.